Analysis of adaptation through segmented linear regression. 1. Foundations - da Silva, João Gilberto Corrêa (Pesquisa Agropecuaria Brasileira, 1995)
The method of simple linear regression of Finlay & Wilkinson (1963), extended by Eberhart & Russell (1966), has been the most used to characterize the phenotypic stability and adaptability of cultivated plants. This method, however, does not allow the identification of the distinct behaviors of the responses of genotypes to the variation of the environment. Particularly, it is not appropriate to identify genotypes with the desirable characteristics, that is, which are responsive to favorable or improved environments and maintain reasonable production in adverse environments. With this reasoning, Silva & Barreto (1985) propose to represent the response of a genotype to a range of environments by a graph composed of two segments of straight line, connected in the point corresponding to the null environment index. This paper explains the foundations of this method and its approach as an extention of the simple linear regression method to allow broader flexibility for the characterization of the distinct behaviors of genotype responses to the environment variation. The application of the method will be illustrated in paper to follow.